Energy Imbalance and Evapotranspiration Hysteresis Under an Advective Environment: Evidence From Lysimeter, Eddy Covariance, and Energy Balance Modeling. Issue 1 (11th January 2021) - Dhungel, Ramesh; Aiken, Robert; Evett, Steven R.; Colaizzi, Paul D.; Marek, Gary; Moorhead, Jerry E.; Baumhardt, R. Louis; Brauer, David; Kutikoff, Seth; Lin, Xiaomao
Abstract: Surface energy imbalance problems have been underexplored especially under advective environments. Here, we present a novel analysis of surface energy fluxes from three distinct approaches—weighing lysimeter, eddy covariance (EC), and surface energy balance modeling for the 2014 sorghum and 2016 corn crop seasons in Bushland, Texas. Our results suggest that energy imbalance problems in the EC system were evidently associated with two opposite evapotranspiration (ET) hysteresis patterns with respect to net radiation and water vapor pressure deficit (VPD). The lysimeter ET had the smallest ET hysteresis while the eddy covariance ET results indicated the strongest hysteresis with respect to net radiation. Conversely, the lysimeter ET hysteresis related to water VPD was stronger than that of the eddy covariance method. This study provides understanding of ET hysteresis patterns, energy imbalance, and advective conditions associated with turbulent flux dynamics for both diel and crop growing seasonal timescales in Bushland, Texas. Plain Language Summary: Water scarcity challenges sustainable development of water resources and food security. Advective environments compound these challenges as hot, dry air parcels frequently travel into the irrigated (wet) crop areas. In such environments, crop evapotranspiration (water loss from crop fields into the atmosphere) could be significantly amplified. We used three distinct methods to characterize not only water loss from crop systems to the atmosphere but also its daily and crop season patterns. From the energy conservation principle, the energy consumed by evapotranspiration (ET) must be balanced, however, the measurements and modeling of these energy components are not exactly balanced. We studied these energy balance components to examine energy imbalance problems and ET delays. Our observations and analysis indicated changes in ET delays and that energy imbalance problems are associated with ET estimates in both sorghum and corn fields. Key Points: Novel analysis of surface energy imbalance problems provide unique insight into evapotranspiration uncertainties Lysimeter weighed the smallest evapotranspiration hysteresis with respect to net radiation and eddy covariance had the largest and vice versa for vapor pressure deficit The findings ultimately help to develop more reliable schemes for partitioning turbulent fluxes in surface energy balance systems